Analysis Assessment, Psychotest, and Leadership Development for Organization Sustainability in The University - Supardi, Supardi; Jumawan; Suroso, Sugeng (International Journal of Advanced Multidisciplinary, 2023)
Purpose To prove by using scientific articles derived from international reputation journals by looking at whether there is really an influence between variables, research methods in the form of literature review by proving whether it is true between variables with this study, the results of this research study support the results of existing studies with variables related to this variable, but limitations in search and for researchers others to continue or use this differentiating variable as future research.